2013
DOI: 10.5433/1679-0359.2013v34n5p2497
|View full text |Cite
|
Sign up to set email alerts
|

Consumo, digestibilidade dos nutrientes e características ruminais de cordeiros alimentados com níveis crescentes de concentrado em ambiente tropical no Vale do Alto Guaporé - MT

Abstract: ResumoObjetivou-se avaliar níveis crescentes de concentrado na dieta de cordeiros sobre o consumo e coeficiente de digestibilidade total (CD) dos nutrientes, características ruminais, temperatura corporal e retal. Foram utilizados quatro cordeiros sem raça definida (SRD), não castrados, com peso corporal (PC) médio de 19,3 Kg ± 2,07 por meio de um delineamento em quadrado latino 4 x 4. Os animais foram alojados em gaiolas de metabolismo, os quais foram alimentados duas vezes ao dia, com dieta composta por sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
3
14
0
5
Order By: Relevance
“…The observed values for ADF digestibility in this study are close to the observed variation in the literature (CUNHA et al, 2009;GERON et al, 2013, LEITE et al, 2013, of 61.00% to 36.43%, for sheep rations containing agribusiness residues.…”
Section: Variablessupporting
confidence: 77%
See 2 more Smart Citations
“…The observed values for ADF digestibility in this study are close to the observed variation in the literature (CUNHA et al, 2009;GERON et al, 2013, LEITE et al, 2013, of 61.00% to 36.43%, for sheep rations containing agribusiness residues.…”
Section: Variablessupporting
confidence: 77%
“…A study conducted by Geron et al (2013), with lambs fed with 20%, 40%, 60%, and 80% concentrates in their diets, showed that on average, diets with 40% concentrate improved DM intake, so the diets used in this study, which had a ratio of 50% concentrate and 50% roughage, was close to the maximum suggested DM intake. This indicated that including 15% RETP in the sheep's diet would not interfere with DM intake and consequently the acceptability of the ration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the fiber content in the diet, the faster the rumen fill and animal satiation (GERON et al, 2013;RIBEIRO et al, 2009; VAN SOEST, 1994;). This was observed in the present study because DM intake increased with supplementation level, and feed intake was lower in non-supplemented lambs (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Determining the appropriate level of concentrate in the animal diet can also prevent feed waste in the feedlot and improve performance during the growing and finishing phases (GERON et al, 2013). Thus, this study aimed to evaluate the performance of feedlot crossbred ewe lambs and the digestibility of diets with increasing levels of concentrate during the growing and finishing phases.…”
Section: Introductionmentioning
confidence: 99%